PROGAM TAHUN KUNJUNGAN MUSEUM RONGGOWARSITO 2012 - Rismahendra Aditya; wiwik widayati; sulistyowati . (Journal of Politic and Government Studies, 2015)
ABSTRACTMuseum Ronggowarsito Central Java is one of the oldest museums in Semarang, Central Java. However, high potential that the museum has not obtained tourist attraction. The current number of visitors Museum Ronggowarsito Central Java has decreased continuously especially during the years 2010 - 2012. This makes the need for programs in Museum Ronggowarsito Central Java in order to raise their visit and find out what programs are carried out by the government to increase visits.This study is a qualitative research. The data source for this study is primary data obtained from interviews with sources and informants. Data analysis was performed with the interactive model analysis.Based on the results of research, Museum Ronggowarsito Central Java programs currently are not able to increase the number of tourists visiting Museum Ronggowarsito Central Java, system collection demonstration at Museum Ronggowarsito Central Java is still less representative, and Museum Ronggowarsito Central Java should increase promotional programs to increase tourist visits to the Museum of Central Java Ronggowarsito. Keywords: years of visits, visits, program